Maturação, compostos bioativos e capacidade antioxidante de frutos de genótipos de Cajazeiras do BAG EMEPA-PB - Silva, Fernanda Vanessa Gomes da (2010)
The study aimed to evaluate the development, physiology of maturation and quality of fruits from genotypes of yellow mombin tress becomes from seeds (progeny) and stalks (clones), and the antioxidant capacity during development in different stages of maturation. The study was divided into four experiments. The first experiment evaluated the processes of growth and maturation of fruits of twelve genotypes of yellow mombin tree, five progenies and seven clones. The development of inflorescences was escorted until the formation and complete maturation of the fruits. According to the results, the genotypes studied showed different cycles of full development, especially during the ripening stage. The fruits had a rapid growth until the beginning of ripening, where from there the fruits showed lower rates of increase in length, diameter and accumulation of fresh and dry weights. The fruit volume increased steadily throughout the period of development. The physicochemical properties of soluble solids, reducing sugars, total sugars and carotenoids increased with advancing maturity. There was a decline in titratable acidity, starch and chlorophyll with the maturation. The development cycle of yellow mombin fruit, from flower opening to fruit ripening, corresponding to an average of 126 days. In experiment II were evaluated the changes occurred during the ripening of fruits of progeny genotypes and clones of yellow mombin tree to establish the stage of maturation and maturity indices most appropriate for the fruit harvest. Fruits of twelve genotypes were selected, and these plants were six progeny and six were cloned. The fruits were harvested and separated into seven stages of maturation described according to Munsell color chart. According to the results, there has been progress in fruit color, evolving gradually from fully green to fruits with orange predominance. The levels of soluble solids (SS) increased with the advancing of maturation. The soluble solids (SS) increased with the advancing of ripening. The SS / AT ratio increased due to intensification of sweetness and acidity reduction making the fruit more palatable. The yellow mombin fruits that showed the best physicochemical characteristics were those from progeny genotype G2. The experiment III evaluated the presence of bioactive compounds, polyphenols and antioxidant capacity of yellow mobin fruits in different stages of maturation from progeny genotypes and clones. Fruits of twelve genotypes were selected, six progeny and six clones. The fruits were harvested in seven maturity stages taking into account the external color of the peel. The levels of total extractable polyphenols and antioxidant capacity were evaluated taking into account the percentage of inhibition of oxidation. According to the results, it was found that the amount of extractable polyphenols ranged from 21.50 to 200.65 mg.100g-1. Generally the fruits of cloned genotypes had higher average for the concentration of extractable polyphenols in relation to progeny genotypes. Regarding the antioxidant capacity of fruits that higher percentages of oxidation inhibition were from genotypes clones. The experiment IV evaluated the presence of bioactive compounds and antioxidant capacity of yellow mombin fruits becomes from progeny and clones during development until the complete maturation. Fruits of twelve genotypes of yellow mombin tree were evaluated, five projeny and seven cloned. The levels of total extractable polyphenols, chlorophyll, carotenoids, flavonoids and antioxidant capacity yellows were quantified taking into account the percentage of inhibition of oxidation and antioxidant activity. It was found that there is a positive correlation between the levels of bioactive compounds and antioxidant capacity.